The Role of SWOT Analysis in Corporate Strategic Decision-Making - Miftakhul Jannah; Anisa Faizah; Aimee Josephira; Vania Puspita; Rusdi Hidayat (JIECIs - Journal of Islamic Economics and Contemporary Issues, 2026)
This study aims to analyze the role of SWOT analysis and the strategy matrix in the process of corporate strategic decision-making. This research uses a literature review approach with a conceptual study design, in which data were obtained from various literature sources in the form of textbooks and scientific journal articles relevant to the topics of strategic management and decision-making. The results of the study indicate that SWOT analysis functions as an analytical framework that helps companies identify internal factors, namely strengths and weaknesses, as well as external factors, namely opportunities and threats, that influence strategic decision-making. In addition, the SWOT matrix serves as an integrative tool that transforms the results of SWOT analysis into structured strategic alternatives through SO, WO, ST, and WT strategies. The findings of this study show that SWOT analysis and the strategy matrix not only function as tools for mapping strategies but also as an analytical framework that supports systematic strategic decision-making. This research provides a conceptual contribution in strengthening the understanding of the role of SWOT analysis in strategic management.